Contraceptive Methods in Diabetic Women Referring to Government Diabetes Clinics in Northern Iran - Mansour-Ghanaei, Roya; Donyaei-Mobarrez, Yalda; Abouzari-Gazafroodi, Kobra (Makara Journal of Health Research, 2023)
Background: Unwanted pregnancies in diabetic women can endanger the mother and the fetus. The present study was conducted to determine contraceptive methods for diabetic women referred to government diabetes clinics in the north of Iran. Methods: A total of 153 diabetic women referred to government clinics in Guilan were included in this cross-sectional study. A questionnaire made by the researcher regarding personal and social information and information related to contraceptive methods was administered. Data were analyzed analytically using SPSS version 19. Results: The findings of the present study revealed that 87.6% of diabetic women used contraceptive methods, of which 44.4% utilized low-effective contraceptive methods (withdrawal method and condoms), and 43.2% opted for highly effective contraceptive methods (tubal ligation, oral contraceptive pill, intrauterine device, and vasectomy). Decision regarding the choice of contraceptive methods was mainly made by couples, followed by consultation with a doctor. Conclusions: A relatively high percentage of diabetic women use less effective contraceptive methods, and the decision to use contraceptive methods is made mainly by couples. Therefore, targeted reproductive health interventions and providing counseling services as part of medical care for diabetic women seem necessary.